ANALISIS YURIDIS AKIBAT PERLUASAN MAKNA PASAL 29 UNDANG-UNDANG NO. 1 TAHUN 1974 TERHADAP UNDANG-UNDANG NO. 37 TAHUN 2004 - Maulana Ibrahim; Sunarmi Sunarmi; Hasim Purba; Mahmul Siregar (JURNAL JUSTIQA, 2021)
Constitutional Court Decision No.69/PUU-XIII/2015 on Article 29 of the Marriage Law No. 1 of 1974 concerning Marriage caused the rules regarding marriage agreements to change, where previously a marriage agreement could only be made before or at the time of marriage. This research is a normative legal research with analytical descriptive character. The approach used is a conceptual approach. Sources of data used in the form of secondary data. The location of the research was held at the Medan District Court class 1 A specifically by interviewing Judges and also interviewing Notaries. This research was conducted by means of literature/document studies and interviews. Data analysis was carried out qualitatively. The results showed that with the Decision No. 69/PUU-XIII/2015, there are two things that become the ratio decidendi of the Constitutional Court to grant the petition for a judicial review of Article 29 of the Marriage Law. First, because of the needs of people who are married to foreign nationals. Second, the Constitutional Court evaluates it in terms of justice. The marriage agreement can be made at any time as long as it is still in the marriage bond. As a result of the decision of the Constitutional Court on the extension of the marriage agreement to the bankrupt debtor, namely the opening of the bankrupt debtor's opportunity to make a marriage agreement, but still the marriage agreement is made within one year before being declared bankrupt so that if it is made during bankruptcy and there is a third party who is harmed, the marriage agreement is canceled for The law is considered to never exist because it is not in accordance with Article 1320 of the Civil Code. That way, the marriage agreement must still not harm the other party.